2013
DOI: 10.4103/0300-1652.110052
|View full text |Cite
|
Sign up to set email alerts
|

MR urography: Anatomical and quantitative information on congenital malformations in children

Abstract: Background and Aim:Magnetic resonance urography (MRU) is considered to be the next step in uroradiology. This technique combines superb anatomical images and functional information in a single test. In this article, we aim to present the topic of MRU in children and how it has been implemented in Northern Greece so far. The purpose of this study is to demonstrate the potential of MRU in clinical practice. We focus both on the anatomical and the quantitative information this technique can offer.Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…The role of CTU in children with suspected CAKUT is different – it is performed to visualize the anatomy of the abnormality [35] and adequate and homogeneous opacification of the hydronephrotic collecting system is crucial. In MRU studies, furosemide causes uniform distribution of the gadolinium contrast within the urinary tract and it is recommended in adults and children, for non-dilated as well as obstructed urinary tract evaluation [7, 11, 13, 36]. However, our analysis showed that there can be no similar effect in CTUs performed in hydronephrotic kidneys in children, and use of furosemide does not change CM distribution in a dilated collecting system.…”
Section: Discussionmentioning
confidence: 67%
“…The role of CTU in children with suspected CAKUT is different – it is performed to visualize the anatomy of the abnormality [35] and adequate and homogeneous opacification of the hydronephrotic collecting system is crucial. In MRU studies, furosemide causes uniform distribution of the gadolinium contrast within the urinary tract and it is recommended in adults and children, for non-dilated as well as obstructed urinary tract evaluation [7, 11, 13, 36]. However, our analysis showed that there can be no similar effect in CTUs performed in hydronephrotic kidneys in children, and use of furosemide does not change CM distribution in a dilated collecting system.…”
Section: Discussionmentioning
confidence: 67%
“…8 Urothelial carcinomas can be seen as a sessile filling or polypoid filling. 9 In present study, 4 cases of renal cell carcinoma, 2 cases of ureteral carcinoma and 3 cases of carcinoma of bladder are identified. We used static as well as excretory urography sequences in cases of tumours.…”
Section: Renal Carcinomamentioning
confidence: 94%
“…Primjer rezultata funkcionalne analize mokraćnog sustava tijekom fMRU nakon obrade uz pomoć programa CHOP-fMRU prikazuje tablica 2. Iako se i danas kao metoda izbora za procjenu funkcije bubrega koristi renalna scintigrafija, danas sve više kompa rativnih studija pokazuje podudarne rezultata scin tigrafije i fMRU-a u procjeni bubrežne funkcije 27,[28][29][30][31] .…”
Section: Magnetno Rezonantna Urografija (Mru) I Funkcionalna Magnetno...unclassified